Political Spillovers of Worker Representation: With or Without Workplace Democracy? - Uwe Jirjahn (Institute of Labor Economics (IZA), 2025)
A series of studies show that unions and works councils have an influence on workers' political activities and attitudes. However, at issue are the transmission channels through which worker representation impacts workers' political activities and attitudes. This article discusses from a theoretical and empirical viewpoint whether the influence of worker representation reflects increased workplace democracy. The article also discusses possible policy implications.
Keywords: D70; J51; J53; K31; O35; 330; party preferences; political engagement; works councils; trade unions; democratic leadership; autocratic leadership